English for international tourism : intermediate teacher's book. - Bailey, Amanda, ....- (Harlow : Longman, 2003)
English for International Tourism is a multi-level course for students who need English for professional communication in the hotel and tourism industries. Illustrated with material from Dorling Kindersley's Eyewitness Travel Guide series and authentic material from companies within the tourist industry this, the intermediate level book, presents effective communication strategies for workplace situations such as giving advice, taking bookings and dealing with complaints. Language awareness is developed through an integrated syllabus that focusses on key grammar, skills, vocabulary and pronunciation.
Keywords: Engels -- Toerisme; Go international; International office